We will rise again : speculative stories and essays on protest, resistance, and hope - Lord, Karen, 1968-; Newitz, Annalee, 1969-; Older, Malka, 1977-; Anders, Charlie Jane; Basu, Samit; Buckell, Tobias S.; Eveleth, Rose, 1987-; Goh, Jaymee; Griffith, Nicola; Heredia, Alejandro, 1994-; James, Vida; Jemisin, N. K.; et al. (Saga Press, 2025)
"In this collection, editors Karen Lord, Annalee Newitz, and Malka Older champion realistic, progressive social change using the speculative stories of writers across the world. Exploring topics ranging from disability justice and environmental activism to community care and collective world building, these imaginative pieces from writers such as NK Jemisin, Charlie Jane Anders, Alejandro Heredia, Sam J. Miller, Nisi Shawl, and Sabrina Vourvoulias center solidarity, empathy, hope, joy, and creativity. Each story is grounded within a broader sociopolitical framework using essays and interviews from movement leaders, including adrienne maree brown and Walidah Imarisha, charting the future history of protest, revolutions, and resistance with the same zeal for accuracy that speculative writers normally bring to science and technology. Using the vehicle of ambitious storytelling, 'We Will Rise Again' offers effective tools for organizing, an unflinching interrogation of the status quo, and a blueprint for prefiguring a different world."--Publisher description.